Enhancement of water level control system (hardware development) / Sahrul Azizi Sulaiman - Sulaiman, Sahrul Azizi (1998)
The tree major task of process control system is to control, monitor and record. Computer are advantageous for following reason: they are able to centralize all the plant data, disseminate it whatever it is needed and provide control strategies at whatever levels are found necessary. Therefore, our project aim is to make use of computer capability by then increasing efficiency and economy in Process Operation. Our project title is so-called Enhancement of Liquid/Water Level Control System. This system is specially designed for controlling water level for single tank for not only human controlled but also computer-controlled.